2015
DOI: 10.3354/dao02885
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characteristics of cyprinid herpesvirus 2: effect of kidney extract supplementation on growth

Abstract: Herpesviral hematopoietic necrosis caused by goldfish hematopoietic necrosis virus (now identified as cyprinid herpesvirus 2, CyHV-2) has contributed to economic losses in goldfish Carassius auratus culture and is becoming a major obstacle in Prussian carp C. gibelio aquaculture in China. Several reports have described difficulties in culturing the virus, with the total loss of infectivity within several passages in cell culture. We succeeded in propagating CyHV-2 with a high infectious titer in a RyuF-2 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…As Shibata et al . () reported that total infectivity of the virus culture was lost after incubation at 35 °C for 1 day, it was thought that the virus in culture medium lost infectivity during incubation at 34 °C for 4 days in this study; however, the reappearance of CPE could be attributed to virus that was reactivated within the cells. The same phenomenon has been reported for KHV, which is closely related to CyHV‐2.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…As Shibata et al . () reported that total infectivity of the virus culture was lost after incubation at 35 °C for 1 day, it was thought that the virus in culture medium lost infectivity during incubation at 34 °C for 4 days in this study; however, the reappearance of CPE could be attributed to virus that was reactivated within the cells. The same phenomenon has been reported for KHV, which is closely related to CyHV‐2.…”
Section: Discussionmentioning
confidence: 56%
“…This observation is consistent with in vitro virus propagation in the goldfish fin RyuF‐2 cell line which occurred within 24 h after inoculation at 25 °C (Shibata et al . ). These infected fish were then kept at 34 °C, a temperature that is non‐permissive to virus replication, and virus propagation in fish tissues was halted.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations